(untitled) (Balneo and PRM Research Journal, 2025)
Background: Osteoporosis is the most common metabolic bone disease with serious physical, psychosocial and economic consequences. It is a chronic, asymptomatic, progressive disease with multifactorial aetiology, characterized by reduced bone mineral density and microarchitectural deterioration of bone tissue; Methods: A retrospective study was conducted, which included an initial cohort of 243 patients hospitalized between January 2023 and December 2023 at the County Emergency Hospital of Sibiu, Clinical Endocrinology Department ; Results: Study results suggest that assessment of bone mineral density (BMD) remains a primary standard in the diagnosis of osteoporosis, as measured by T and Z scores from DXA densitometry. However, biomarkers such as total calcium, ionic calcium, vitamin D, phosphorus, PTH and bone degradation markers (e.g. Beta Crosslaps) play a significant role in assessing bone metabolism and identifying fracture risk; Conclusions: The study highlights the importance of screening in postmenopausal women and the need for calcium and vitamin D supplementation in patients with osteoporosis or osteopenia.